SISTEM PRAKERIN BERBASIS WEBSITE MENGGUNAKAN METODE UCD STUDI KASUS DI SMK DHARMA WANITA KROMENGAN - Susanto, Gaguk; Budi Pranata, Kurriawan; Rofiq Zain, Mohammad; Syahminan (Department of System Information, 2024)
The internship activity is an internship activity for Dharma Wanita Kromengan Vocational School students in an industrial environment for 6 months. However, there are various obstacles that occur when carrying out internship activities, including 1) Difficulty for admin in grouping internship students according to places in the world of business and industry (dudi) because zoning is recorded manually. 2) The low effectiveness of field supervisor teachers in monitoring students' activities every day at the internship site, because attendance and journals of students' daily activities are still recorded manually. 3) Recording is not recorded as a function of time, so there are cases of dishonesty when filling in the daily journal which is ultimately written at the end of the internship activity. 4) The attendance journal is damaged or torn or even lost. Based on the analysis of these problems, this research aims to monitor internship activities periodically, in an orderly and disciplined manner. Therefore, it is important to create a website-based internship system application using the Ucer Centered Design (UCD) method which can be accessed by students to record activities during internship and monitored by the internship coordinator as admin, field supervisor teacher and supervisor at the internship site as evaluator and evaluator. The results of the application created provide a feasibility response which was carried out using the User Acceptance Test (UAT), obtaining an average percentage for admins of 86.81%, teachers 87.80%, supervisors 88.19% and students 87.66%.